Pengaruh Pertumbuhan Ekonomi, Upah Minimum Provinsi dan Tingkat Pendidikan terhadap Tingkat Partisipasi Angkatan Kerja di Provinsi Jambi Tahun 2009-2023 - Fathiyah, Fathiyah; Syukri, Muhammad; Masnun, Masnun; Rahmadani, Indah (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The purpose of this study is to determine the effect of economic growth, provincial minimum wage, and education level simultaneously and partially on the Labor Force Partippcipation Rate in Jambi Province in 2009-2023. The data used in this study is secondary data published in the form of a time series for 15 years starting from 2009-2023 in Jambi Province. The source of data obtained from the agency is the Central Statistic Agency (BPS) in Jambi Province. This study used multiple linear regression analysis tools, and data analysis prerequisite test using normality, multicollinearity, autocorrelation, and heteroscedasticity tests. The hypothesis test used are the coefficients of determination (R2), F test and T test. The result of this study show simultaneously that: Economic Growth, Provincial Minimum Wage, and Education Level do not affect the Labor Force Participation Rate in Jambi Province in 2009-2023. And Partially : (1) Economic Growth does not affect the Lbor Force Participation Rate, (2) The Provincial Minimum Wage does not affect the Labor Force Participation Rate. (3) The Level of Education does not affect the Labor Force Participation Rate in Jambi Province 2009- 2023.